Medical Grabbing Servo System with Friction Compensation Based on the Differential Evolution Algorithm - Yeming Zhang (SpringerOpen, 2021)
Abstract This paper introduces a pneumatic finger cylinder servo control system for medical grabbing. First, according to the physical structure of the proportional directional valve and the pneumatic cylinder, the state equation of the gas in the servo system was obtained. The Stribeck friction compensation model of a pneumatic finger cylinder controlled by a proportional valve was established and the experimental platform built. To allow the system output to better track the change in the input signal, the flow-gain compensation method was adopted. On this basis, a friction compensation control strategy based on a differential evolution algorithm was proposed and applied to the position control system of a pneumatic finger cylinder. Finally, the strategy was compared with the traditional proportional derivative (PD) strategy and that with friction compensation. The experimental results showed that the position accuracy of the finger cylinder position control system can be improved by using the friction compensation strategy based on the differential evolution algorithm to optimize the PD parameters.